Evaluation of the Teaching Factory Class Implementation Program at the Center of Excellence Vocational School (Case Study in the Mechanical Engineering Skills Competency at SMKN 3 Metro) - Umi Aisyah; Widiani Trisnaningsih; Riswanti Rini (Journal of Educational Research, Evaluation and Supervision, 2025)
This research aimed at evaluating Teaching Factory Class program implementation in the Mechanical Engineering Skills Competency of SMKN 3 Metro. It is a Vocational School Center of Excellence, a program held by the Indonesian Ministry of Education. The evaluation was carried out by using the CIPP (Context, Input, Process, Product) model. It was intended to analyze the effectiveness of the program in preparing competent graduates according to the needs of the business and industrial world. The research was qualitative, using the case study method. Data collection was carried out through 1) in-depth interviews with school principals, the vice principal of curriculum, the vice principal of public relations, the vice principal of infrastructure, productive teachers, industrial instructors, and students; 2) observation of the Teaching Factory learning process; and 3) documentation studies. The research results show: (1) In context, this program is relevant to industrial needs and vocational education policies but still requires strengthening in the aspect of market needs analysis; (2) In terms of input, teacher qualifications and practical facilities are adequate, but optimization is needed in the use of learning facilities; (3) The learning process has adopted an industrial atmosphere, although there are still obstacles in synchronizing schedules with industry; (4) Graduate products show increased technical competence and soft skills, with a good level of job absorption in industry. Research recommendations include strengthening industry partnerships, developing teacher competencies, optimizing practice facilities, and improving the industry-based assessment system.